From Dust to DUST to Dust: Asbestos and the Struggle for Worker Health and Safety at Bendix Automotive - Storey, Robert; Lewchuk, Wayne (Labour/Le Travailleur, 2000)
Abstract In the mid-1970s workers and local union activists at Bendix Automotive in Windsor, Ontario, became aware that the brake shoes they manufactured contained asbestos and that the dust that regularly filled the air in sections of the company's two plants contained asbestos dust. Within the context of growing concern among Ontario workers and unions for greater health and safety protection, workers and local United Automobile Workers' (UAW) union activists at Bendix pressured the company and the Ontario government to clean up and/or eliminate asbestos from their workplace. In the midst of this struggle Bendix management announced that, for solely economic reasons, it was closing down its operations in Windsor. The shutdown, roundly decried by Bendix workers and union activists, nevertheless highlighted the tensions and contradictions confronting workers and unions in the area of heath and safety. That is, while Bendix workers wanted their workplace to be safe and healthy, they also wanted and needed their jobs. At the same time, local and national union UAW officials, while trying to secure a safe and healthy working environment for their members, confronted the possibility of the plant shutting down if they pushed too hard on asbestos. In the end, the ability of Bendix to close down its operations, with minimal legal and no statutory sanctions, demonstrated the power of corporate capital and the conflicting and constrained nature and extent of workers' choices under capitalism in the arena of worker health and safety.